2009
DOI: 10.1007/s00705-009-0408-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of vaccine-virus-associated rabies cases in red foxes (Vulpes vulpes) after oral rabies vaccination campaigns in Germany and Austria

Abstract: To eradicate rabies in foxes, almost 97 million oral rabies vaccine baits have been distributed in Germany and Austria since 1983 and 1986, respectively. Since 2007, no terrestrial cases have been reported in either country. The most widely used oral rabies vaccine viruses in these countries were SAD (Street Alabama Dufferin) strains, e.g. SAD B19 (53.2%) and SAD P5/88 (44.5%). In this paper, we describe six possible vaccine-virus-associated rabies cases in red foxes (Vulpes vulpes) detected during post-vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 30 publications
1
44
0
4
Order By: Relevance
“…It has been reported that the ERA and SAD strains used for vaccination of animals can, on rare occasions, have been linked with clinical disease in both experimental models and vaccinated wild animals. [12] [13] [14] [15] [16] [17]. Currently, the ERA strain is used in the production of live-attenuated RABV vaccine in China, contradictory to the requirement of WHO [18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the ERA and SAD strains used for vaccination of animals can, on rare occasions, have been linked with clinical disease in both experimental models and vaccinated wild animals. [12] [13] [14] [15] [16] [17]. Currently, the ERA strain is used in the production of live-attenuated RABV vaccine in China, contradictory to the requirement of WHO [18].…”
Section: Introductionmentioning
confidence: 99%
“…One case of rabies in foxes following oral administration of the SAD B19 virus for immunization was observed in Austria (Vanek et al 2004). Four foxes with rabies induced by the SAD B19 virus were found in Germany during the oral vaccination campaigns against rabies in 2001, 2002, 2004(Mueller et al 2005. Sixteen cases of post-vaccination rabies were recorded in Canada in 1989-2004 in 4 red foxes, 2 raccoon dogs, 2 skunks and 1 calf among other animals (Brasilia RITA meeting 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for this include the increasing population density of foxes, their susceptibility to relevant pathogens, their hunting preference for small mammals which leads to frequent ingestion of intermediate hosts, and their wide distribution and vicinity to human settlements as a consequence of their synanthropic lifestyle (Wandeler et al., 2003; Deplazes et al., 2004; Duscher et al., 2005, 2006; Torina et al., 2013). The red fox was the main reservoir for sylvatic rabies in Central Europe, which was very common and a threat to human and animal health before the oral fox vaccination campaign which started in the 1980s in Austria (Müller et al., 2009). Due to the intensive surveillance and baiting, rabies is now considered eradicated from Austria.…”
Section: Wildlife Animals As Reservoir For Zoonotic Pathogens and Vecmentioning
confidence: 99%